2010
DOI: 10.1200/jco.2009.27.6204
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Chemotherapy Plus Surgery Versus Surgery Plus Adjuvant Chemotherapy Versus Surgery Alone in Early-Stage Non–Small-Cell Lung Cancer

Abstract: In early-stage patients, no statistically significant differences in disease-free survival were found with the addition of preoperative or adjuvant chemotherapy to surgery. In this trial, in which the treatment decision was made before surgery, more patients were able to receive preoperative than adjuvant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
214
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(239 citation statements)
references
References 22 publications
12
214
0
7
Order By: Relevance
“…Moreover, implementation of adjuvant treatment does not significantly affect disease free survival (DFS) in earlystage LC patients (89). However, the benefits of neoadjuvant and/or adjuvant treatment in five-year survival after pneumonectomy for LC stage III patients are also reported in literature (40).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, implementation of adjuvant treatment does not significantly affect disease free survival (DFS) in earlystage LC patients (89). However, the benefits of neoadjuvant and/or adjuvant treatment in five-year survival after pneumonectomy for LC stage III patients are also reported in literature (40).…”
Section: Discussionmentioning
confidence: 99%
“…In the CALGB 9633 study, postoperative paclitaxel (PTX) plus CBDCA was found to be effective for tumors ≥4 cm in pathological stage IB [14]; however, in the NATCH study, it was not effective for early-stage lung cancer [15]. In the Four-Arm Study of platinum doublet for advanced-stage lung cancer, no significant differences were observed in the response rate or OS between PTX plus CBDCA and VNR plus CDDP [16].…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials in stage IA NSCLC did demonstrate that 5-year overall survival is similar when induction therapy followed by resection for cStage-IA was compared to resection followed by adjuvant chemotherapy for pStage-IA (2,3) .…”
Section: Rationale For Mediastinal Nodal Stagingmentioning
confidence: 99%